Comparing the bond strength of fiber post cementation in the root canal using pre- and co-curing procedures with the same self-etching bonding system - I-Chian Chou; Hao-Ting Wang; Yung-Chung Chen; Yi-Fan Hsu; Wei-Hung He (Elsevier, 2022)
Background/purpose: Self-etching bonding systems are widely used in fiber post cementation. However, no clear guidelines are established for choosing pre- or co-curing procedures. We investigated the bond strength of fiber post cementation using pre-/co-curing methods in self-etching bonding systems and compared them with those of a self-adhesive system. Materials and methods: Post spaces were prepared in 30 single-rooted premolars/canines, and the fiber posts were cemented in three ways (10 specimens per group): using a self-etching bonding system with either a pre-curing or simultaneous co-curing procedure (RelyX™ Ultimate; groups SE-pre and SE-co, respectively) and using a self-adhesive system (RelyX™ Unicem 2, group SA). Each specimen was embedded and sliced perpendicularly to the long axis into three 2.5-mm-thick sections. Microphotographs of the coronal and apical surfaces of each section were acquired, and push-out tests (1 mm/min) were performed. One-way analysis of variance was conducted on the data, followed by Tukey's honestly significant difference post hoc test. Results: The bond strength in the whole root was not significantly different among the three groups. When independently evaluating each portion, group SE-co exhibited significantly lower coronal bond strength. The bond strength varied among root regions only in group SE-pre; the apical region had a significantly lower value. Conclusion: No cementation method is superior in all portions. Regarding pre-curing methods, clinicians must caution the fit between the post and post space, which may be affected by the pre-polymerized bond layer. The co-curing method used in a larger coronal cement space contributes to the poor bond strength.